Balancing exploration and exploitation in public management: Proposal for an organizational model. Issue 3 (5th August 2020) - Palmi, Pamela; Corallo, Angelo; Prete, M. Irene; Harris, Phil
Abstract : Over the last 30 years, a wave of reforms has reshaped the panorama of public administrations around the world, which have also stimulated debates on the subject reform in public sector relations. Much research has focused on discussing the validity of New Public Management (NPM) as a paradigm, including the recognition of regional versions of a number of universal problems in the Public Governance, NPM, and Public Value areas. This debate is focused on the need to give concrete answers to the new management needs of policy makers and to the growing demands of citizens. Increasingly public administration is based on meeting two needs: society requires creative, flexible, and innovation‐oriented approaches, whilst economic pressures and budget cuts are forcing uses and models oriented toward efficiency, competitiveness, and cost savings. As regard the changing requirements of the public government, the new organizational system needs to incorporate the creativity, innovation capacity, and flexibility necessary to achieve sustainability and public value. The purpose of this research is to offer an organizational model, which balances exploration activities with those of exploitation, thus being able to meet the changing needs within the Administration, and the actions envisaged for its operations. This article also introduces the requirements for a decision support system to measure regional performance and service quality. It is hoped that we add to our knowledge and understanding of coordinated public policy and good governance that is effective even in these radically demanding Covid‐19 times.